UNIVERSITY STUDENTS’ PERCEPTIONS OF RESIDENTIAL RENTAL ORGANIZATIONS’ CORPORATE SOCIAL RESPONSIBILITY AND SERVICE MARKETING MIX AND THEIR INFLUENCES ON THE STUDENTS’ LOYALTY TO THE ORGANIZATIONS - รอดภัย ชำนาญ; สุขเสริม ธรรมวิมล (Journal of Management Science Chiangrai Rajabhat University, 2018)
This study was a survey research that aimed to investigate students’ perceptions of corporate social responsibility and the service marketing mix of the dormitory business which were surrounding Ubon Ratchathani University (UBU), and the manner in which these influenced students’ loyalty to the dormitory business. The participants were 374 students who rented dormitories around the university. Data were collected by the use of questionnaires and analyzed by the use of percentages, means, standard deviations, independent t-test, One Way ANOVA, correlation coefficient, and multiple regressions. The findings showed that most of the respondents were females with incomes lower than 5,000 baht a month studying in the fourth year in the Faculty of Management Science. They had rented for 1 year and had experience in renting accommodation in the area. The students’ general perception of the rental organizations’ corporate social responsibility and attitude to their service marketing mix were at high levels. Differences in personal factors did not affect loyalty to the rental organizations. The relationships between the students’ perceptions of the organizations’ corporate social responsibility and the students’ loyalty to the organizations were positive, and the same was found between the service marketing mix and loyalty. The factors that affected students’ perceptions of corporate social responsibility and loyalty to rental organizations the most were environmental care and fairness in operation. The one factor that affected the service marketing mix and loyalty to the organizations was physical environment.